Divergent role of PIDA and PIFA in the AlX3 (X = Cl, Br) halogenation of 2-naphthol: a mechanistic study - Juárez-Ornelas, Kevin A.; Solís-Hernández, Manuel; Navarro-Santos, Pedro; Jiménez-Halla, J. Oscar C.; Solorio-Alvarado, César R. (Beilstein Journal of Organic Chemistry, 2024)
The reaction mechanism for the chlorination and bromination of 2-naphthol with PIDA or PIFA and AlX3 (X = Cl, Br), previously reported by our group, was elucidated via quantum chemical calculations using density functional theory. The chlorination mechanism using PIFA and AlCl3 demonstrated a better experimental and theoretical yield compared to using PIDA. Additionally, the lowest-energy chlorinating species was characterized by an equilibrium of Cl–I(Ph)–OTFA–AlCl3 and [Cl–I(Ph)][OTFA–AlCl3], rather than PhICl2 being the active species. On the other hand, bromination using PIDA and AlBr3 was more efficient, wherein the intermediate Br–I(Ph)–OAc–AlBr3 was formed as active brominating species. Similarly, PhIBr2 was higher in energy than our proposed species. The reaction mechanisms are described in detail in this work and were found to be in excellent agreement with the experimental yield. These initial results confirmed that our proposed mechanism was energetically favored and therefore more plausible compared to halogenation via PhIX2.
Keywords: aromatic bromination; aromatic chlorination; density functional theory (DFT); hypervalent iodine; iodine(III)